Human CD141+ dendritic cells (cDC1) are impaired in patients with advanced melanoma but can be targeted to enhance anti-PD-1 in a humanized mouse model. Issue 3 (18th March 2021) - Lee, Yoke Seng; O'Brien, Liam J; Walpole, Carina M; Pearson, Frances E; Leal-Rojas, Ingrid M; Masterman, Kelly-Anne; Atkinson, Victoria; Barbour, Andrew; Radford, Kristen J
Abstract : Background: The conventional type 1 dendritic cell subset (cDC1) is indispensable for tumor immune responses and the efficacy of immune checkpoint inhibitor (ICI) therapies in animal models but little is known about the role of the human CD141 + DC cDC1 equivalent in patients with melanoma. Methods: We developed a flow cytometry assay to quantify and characterize human blood DC subsets in healthy donors and patients with stage 3 and stage 4 metastatic melanoma. To examine whether harnessing CD141 + DCs could improve responses to ICIs in human melanoma, we developed a humanized mouse model by engrafting immunodeficient NSG-SGM3 mice with human CD34 + hematopoietic stem cells (HSCs) from umbilical cord blood followed by transplantation of a human melanoma cell line and treatment with anti-programmed cell death protein-1 (anti-PD-1). Results: Blood CD141 + DC numbers were significantly reduced in patients with stage 4 melanoma compared with healthy controls. Moreover, CD141 + DCs in patients with melanoma were selectively impaired in their ability to upregulate CD83 expression after stimulation with toll-like receptor 3 (TLR3) and TLR7/8 agonists ex vivo. Although DC numbers did not correlate with responses to anti-PD-1 and/or anti-cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) ICIs, their numbers and capacity to upregulate CD83 declined further during treatment in non-responding patients. Treatment with anti-PD-1 was ineffective at controlling tumor growth in humanized mice but efficacy was enhanced by indirectly expanding and activating DCs in vivo with fms -like tyrosine kinase-3 ligand (Flt3L) and a TLR3 agonist. Moreover, intratumoral injections of CD141 + DCs resulted in reduced tumor growth when combined with anti-PD-1 treatment. Conclusions: These data illustrate quantitative and qualitative impairments in circulating CD141 + DCs in patients with advanced melanoma and that increasing CD141 + DC number and function is an attractive strategy to enhance immunogenicity and response rates to ICIs.